Isolated metastasis of hepatocellular carcinoma in the right ventricle: A case report. Issue 51 (December 2016) - Kim, Su Bin; Shin, Yoon Cheol; Kwon, Sung Uk
Abstract : Abstract: Metastatic hepatocellular carcinoma (HCC) of the right ventricle is very rare and difficult to diagnosis. A 79-year-old man who underwent right hemi-hepatectomy for HCC was admitted to our hospital for chest pain, severe dyspnea, and orthopnea. The echocardiogram showed a tumor located in the right ventricle. A biopsy was obtained, and histopathological findings confirmed metastatic HCC. Palliative resection of the tumor was performed. There is no standard treatment for metastatic HCC into the right ventricle. Thus, treatment should be individualized to the patient, and a multidisciplinary approach should be used.